GAYA HIDUP HALAL DALAM PERSPEKTIF MAQASID SYARIAH: MEMBANGUN KESEJAHTERAAN HOLISTIK - Agus Miswanto; Siti Fatimah (Universitas Mathla’ul Anwar Banten, 2025)
This article discusses the halal lifestyle from the perspective of Maqasid Syariah with the aim of building holistic well-being. A halal lifestyle is defined as behavior that is in accordance with Islamic law, encompassing all dimensions of life, not just food and drink. Although this trend is growing rapidly, public understanding is often shallow and limited to food certification. Therefore, this article uses a literature study approach with the Maqasid Syariah framework to analyze the relationship between a halal lifestyle and the five main objectives of sharia (al-dharuriyat al-khamsah). The results show that a halal lifestyle is fundamentally correlated with the protection of religion (Hifdz al-Din), life (Hifdz al-Nafs), reason (Hifdz al-‘Aql), offspring (Hifdz al-Nasl), and property (Hifdz al-Mal). This practice is a form of obedience, maintaining physical and mental health, protecting the mind from harmful substances, forming a harmonious family, and creating a just and sustainable economic system. In conclusion, a halal lifestyle is not just a set of rules, but a comprehensive philosophy of life to achieve true well-being. Maqasid Syariah provides a rational and philosophical foundation, proving that every rule in Islam has a noble purpose to create a balanced, healthy and dignified life.